Large-scale conditions that result in wet summers over arid Western Southern Africa - Kekana, Bohlale (Department of Oceanography, 2025)
The summer (November-April) rainfall patterns across the western region of southern Africa are poorly understood compared to the rest of southern Africa. Although the western interior of southern Africa is considered mostly arid, it is prone to highly variable rainfall and flash floods, impacting vulnerable communities and unique ecosystems. The recent extreme rainfall during 2020/21 and 2021/22 have highlighted the impacts such wet summers can have on vulnerable communities. However, it is not only the rainfall patterns that are poorly understood but also the large-scale drivers that lead to wet conditions across the region. Using a combination of satellite-derived rainfall products and ERA5 reanalysis, this study highlights the complex factors leading to summers with extreme rainfall in this typically arid area over the period 1981-2022. In the analysis, it is highlighted that the wettest conditions typically occur during January to February (JF) and March to April (MA). Departing from traditional approaches, the analysis focuses on ND, JF, and MA to capture variations in circulation changes and rain-bearing system activity. JF stands out with higher rainfall amounts and more rainy days (>10mm), contributing significantly to the overall seasonal rainfall. The seasonal rainfall cycle peaks in February and March, with the rainy season typically spanning from November to April. Spatial distribution emphasizes the region's relative dryness compared to nearby areas, showcasing distinct seasonal fluctuations. Rainfall characteristics, including moderate and heavy rain days, exhibit temporal variability within the seasonal cycle. Furthermore, the significance of late summer rainfall in each bi-monthly period is highlighted. The analysis also highlights considerable interannual variability, with associations between rainfall and climate modes such as the El Niño-Southern Oscillation (ENSO) and the Southern Annular Mode (SAM). However, ENSO stands out as the main driver. There are negative correlations between rainfall and ENSO, suggesting increased (decreased) rainfall during La Niña (El Niño). During the wettest summers, such as 2021 and 2022, there is a notable increase in rainy days compared to the average. This trend aligns with La Niña (El Niño) events, indicating the influence of ENSO on rainfall variability. Positive (negative) standard anomalies during aggregated periods (NDJFMA) correspond to La Niña (El Niño), further emphasizing this relationship. SAM also plays a role, with positive (negative) phases associated with the wettest (driest) years. Cyclonic anomalies over land, particularly in Angola, contribute to widespread rainfall during wet years, while anticyclonic anomalies lead to drier conditions in dry years. These patterns influence subtropical jet streams and storm tracks, impacting seasonal weather and rainfall distribution across southern Africa and neighbouring oceanic regions. Wavenumber 3 or 4 patterns may influence semi-permanent anticyclones in the South Atlantic and South Indian Ocean, affecting regional weather systems. Factors such as moisture flux, divergence patterns, and low level circulation anomalies in the southern Kalahari shape convective rainfall dynamics, with anticyclonic circulation promoting dry conditions and cyclonic circulation facilitating convective activity. Negative omega anomalies in convergence areas indicate favourable conditions for convective rainfall, particularly during La Niña summers. Understanding the strength and intensity of features like the Angola Low or Botswana High could provide further insight into rainfall variability across the region.